The breast lesion excision system (BLES) under stereotactic guidance cannot be used as a therapeutic tool in the excision of small areas of microcalcifications in the breast. Issue 93 (August 2017) - Milos, Ruxandra-Iulia; Bernathova, Maria; Baltzer, Pascal A.; Pinker-Domenig, Katja; Kapetas, Panagiotis; Rudas, Margaretha; Helbich, Thomas H.
Highlights: BLES is a new breast-biopsy device that excises non-fragmented specimens using radiofrequency. BLES allows accurate diagnosis of small areas of microcalcifications. BLES cannot be considered a therapeutic tool in high-risk and malignant lesions. Abstract: Objective: The breast lesion excision system (BLES) is a new, automatic percutaneous breast biopsy device that excises single large specimens using radiofrequency cutting. The aim of this study was to determine whether BLES, under stereotactic guidance, can be used as a therapeutic tool in the assessment of small areas of microcalcifications in the breast by providing samples with clear margins. Material and methods: In this retrospective study, 149 patients with suspicious (BIRADS 4 or 5) small areas of microcalcifications underwent stereotactic-guided BLES. Of these, 34 patients (22.8%) with microcalcifications that had a diameter smaller than the basket size (≤15 mm) underwent both BLES and subsequent surgery. Histopathology findings from BLES and subsequent surgery were compared. Identical, underestimation and total excision findings were assessed. Results: BLES revealed fourteen (41.1%) high-risk lesions, ten (29.4%) ductal carcinomas in situ, and ten (29.4%) invasive cancers. Identical results between BLES and surgery were seen in 17/34 (50%) lesions. Surgery confirmed total excision of BLES in 15/34 (44.1%) lesions. Underestimation was seen in 2/34 (5.8%) lesions. Conclusion: BLES allows accurate diagnosis of small areas of microcalcifications, with few underestimates. BLES is a diagnostic, but cannot be considered to be a therapeutic tool in the case of suspicious microcalcifications because total excision was seen in only 44.1% of these lesions. Studies are needed to address the therapeutic benefit of this procedure in solid lesions.